EFFECT OF OSTEONTM II COLLAGEN IN THE TREATMENT OF CHRONIC PERIODONTITIS PATIENTS: A CLINICAL AND RADIOGRAPHICAL STUDY - GRO , REZAN H.; MOUSA, HASHIM D. (Journal of Duhok University, 2023)
inflammatory disease that lasts for a long time and affects the soft and hard tissues around the teeth. The ultimate goal of periodontal therapy is to regenerate the lost periodontal tissue for optimal function and aesthetics. The aim of this study was to evaluate the clinical and radiographic effects of OsteonTM II collagen, in comparison with open flap debridement (OFD) in the treatment of chronic periodontitis patients.Material and methods: 30 periodontal bony defects in 7 systemically healthy patients that had at least 3 defects, within the age range of 25–40 years, viewing moderate to severe chronic periodontitis were selected and randomly divided into two groups, control group(n=15) was treated by open flap debridement (OFD) alone and test group(n=15) was treated by OFD with placement of OsteonTM II Collagen. All the selected periodontal defects were evaluated with the clinical and radiographic parameters such as plaque index (PI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL), and radiographic defect depth. All the clinical and radiographic parameter values attained at (baseline and 6 months) were subjected to statistical analysis.Results: Significant lessening in PI, GI, PPD, CAL and radiographic defect depth were detected after 6 months of periodontal surgery as compared to baseline in both groups (P<0.05). Superior decrease in PPD, gain in CAL and radiographic defect fill was seen in test group after 6 months.Conclusion: In terms of reducing probing pocket depth (PPD), increasing clinical attachment level (CAL), and filling bone defects, OsteonTM II collagen showed significant clinical, radiographic, and statistical improvements compared to open flap debridement (OFD) alone